Breast cancers with neuroendocrine differentiation: Retrospective case studies series from a single institution based on the 2019 WHO classification - Youngkyung Jeon; Ji-Yeon Kim; Jin Seok Ahn; Young-Hyuck Im; Kyuehee Choi; Sun Young Jeong; Yeji Jung; Jaeyeon Jang; Dae-Ho Choi; Joohyun Hong; Hyo Jung Kim; Soo Youn Cho; et al. (Cancer Treatment and Research Communications)
Background: The World Health Organization's fifth edition of tumor series classification was published in 2019 and adopted the term ‘Neuroendocrine neoplasm (NEN)’ to encompass all tumor classes with predominant neuroendocrine differentiation (NED). Based on the updated classification of the NEN, we conducted a case series using the Clinical Data Warehouse platform of SMC. Methods: In this retrospective study, breast NENs and invasive breast carcinomas no special type (IBCNST) with NED, were defined as 'NENS’. Based on pathology slide findings, a pathologist reclassified the diagnoses. Clinical presentation, tumor characteristics, and clinical outcomes of breast ‘NENS’ were reviewed retrospectively. Results: A total of 34,370 patients were diagnosed with breast cancer from 1995 to 2022 in SMC, and 14 (0.04 %) patients were diagnosed with breast ‘NENS’: eight NECs, three NETs, and three IBCNST with NED. The patients’ median age was 48.5 years. All patients were treated with curative intent surgery; five patients received neoadjuvant chemotherapy, twelve patients received radiotherapy, six patients received adjuvant chemotherapy, and eight patients received hormone therapy. The median follow-up period for the eight patients with breast NEC was 20.4 months. The median disease-free and overall survival were 14.2 months and 23.6 months, respectively. Patients with NET or IBCNST with NED (n = 6) had an overall favorable outcome, with no deaths, with only one case of disease recurrence. Conclusion: The incidence of primary breast NENS’ was very low (0.04 %) in this single-center study. Among them, primary breast NEC was associated with poor overall survival. Novel treatments are thus required to improve the prognosis of primary breast NEC.